Rethinking the WOFOST model to simulate growth and development of Chinese cabbage (Brassica rapa L. ssp. Pekinensis) - Ruoling Tang; Iwan Supit; Fen Zhang; Xiaozhong Wang; Fusuo Zhang; Xuanjing Chen; Xinping Chen; Ronald Hutjes (Agricultural Systems, 2025)

Organic fertilizer substitution for chemical fertilizer has a stronger effect on soil bacterial specialists than on generalists - Ruoling Zhang; Weidong Xu; Hao Liu; Xiang Long; Jiaqing Zhou; Min Xu; Hui Cao; Feng Wang (Plant and Soil, 2025)

Reapplication of glyphosate mitigate fitness costs for soil bacterial communities - Hao Liu; Cunzhi Zhang; Bo Zhang; Weidong Xu; Ruoling Zhang; Liting Zhang; Yue Li; Heming Han; Hui Cao (Journal of Environmental Management, 2025)

Oxidation with potassium ferrate for the one-pot preparation of carboxylated cellulose II nanocrystals - Yunxiao Liu; Xiaolin Li; Yulong Li; Hongze Xu; Ruoling Liu; Yi Zhang; Zhenchao Zhang; Yuan Yuan; Lu Zong; Lijuan Zhou; Jianming Zhang (Carbohydrate Polymers, 2024)

Synergistic association of long-term ozone exposure and solid fuel use with biomarkers of advanced fibrosis - Xiaoyu Hou; Zhenxing Mao; Xiaoqin Song; Ruiying Li; Wei Liao; Ning Kang; Caiyun Zhang; Xiaotian Liu; Ruoling Chen; Wenqian Huo; Chongjian Wang; Jian Hou (Environmental Science and Pollution Research, 2023)

Modelling growth of chili pepper (Capsicum annuum L.) with the WOFOST model - Ruoling Tang; Iwan Supit; Ronald Hutjes; Fen Zhang; Xiaozhong Wang; Xuanjing Chen; Fusuo Zhang; Xinping Chen (Agricultural Systems, 2023)

Effects of Lateral Flows on the Supercavitation and Hydrodynamic Characteristics of Underwater Series and Parallel High-Speed Projectiles - Lite Zhang; Chengwei Zhang; Huixia Jia; Ruoling Dong (Journal of Marine Science and Engineering, 2023)
In this paper, the supercavitation of the parallel and tandem projectiles moving underwater with high-speed under the condition with/without lateral flows is numerically simulated by the volume of fraction (VOF) model. The motion of the projectiles was handled by the overlapping grid and six degrees of freedom (DOF) techniques. The supercavitation evolution and the hydrodynamic characteristics of the projectiles were analyzed for the parallel and tandem projectiles under different conditions. The results show that the cavity shape is symmetrical under the condition without lateral flows, but is no longer symmetrical under the conditions with lateral flows. The asymmetry of the cavity contour increases with the velocity of the lateral flow. For the parallel projectiles, the change trends of the axial velocity of projectile 1 and projectile 2 are nearly the same. The offset velocity of projectile 1 and projectile 2 increases with the increase in the velocity of the lateral flow. The deflection angle of projectile 1 decreases with the increase in the lateral flow velocity but that of projectile 2 increases with the increase in the lateral flow velocity. At t = 3.0 ms, the deflection angle of projectile 2 is up to 20° under the condition of the lateral flow velocity of 11.25%, while the deflection angle of projectile 1 and 2 under other conditions is in the range of 5°. For the tandem projectiles, the axial velocity of projectile 1 gradually decreases. The change trend of the axial velocity of projectile 2 at first is the same as that of projectile 1, and then the change is dependent on the velocity of the lateral flow. Under the condition of the lateral flow velocity with 11.25%Vp, projectile 2 cannot enter the cavity of the front projectile. The change trend of the axial velocity of projectile 2 is similar as but somewhat slower than that of projectile 1. For the parallel projectiles, the ballistic stability of the projectile on the oncoming side is better than that of the projectile on the backflow side. Whether parallel or tandem projectiles, the ballistic stability of projectile 2 becomes worse with the increase in the lateral flow velocity.

Association of air pollution with dementia: a systematic review with meta-analysis including new cohort data from China - Jie Tang; Anthony Chen; Fan He; Martin Shipley; Alan Nevill; Hugh Coe; Zhi Hu; Tao Zhang; Haidong Kan; Eric Brunner; Xuguang Tao; Ruoling Chen (Environmental Research, 2023)

Plantanone D, a new rare methyl-flavonoid from the flowers of Hosta plantaginea with anti-inflammatory and antioxidant activities - Li Yang; Yuye Zhu; Zhongwei He; Tingfang Zhang; Zhixi Xiao; Ruoling Xu; Junwei He (Natural Product Research, 2021)